2020
DOI: 10.1111/1758-2229.12863
|View full text |Cite
|
Sign up to set email alerts
|

Temperature impacts community structure and function of phototrophic Chloroflexi and Cyanobacteria in two alkaline hot springs in Yellowstone National Park

Abstract: Summary Photosynthetic bacteria are abundant in alkaline, terrestrial hot springs and there is a long history of research on phototrophs in Yellowstone National Park (YNP). Hot springs provide a framework to examine the ecophysiology of phototrophs in situ because they provide natural gradients of geochemistry, pH and temperature. Phototrophs within the Cyanobacteria and Chloroflexi groups are frequently observed in alkaline hot springs. Decades of research has determined that temperature constrains Cyanobacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
55
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 63 publications
(75 citation statements)
references
References 60 publications
11
55
0
Order By: Relevance
“…Similar to psb genes, we recovered more copies of both psc and puf genes in sites < 63ºC, suggesting diversity (or taxa) abundance increases with decreasing temperature. These results are consistent with our previous work that suggest phototrophs with type-I RCs are less abundant at high temperatures, while the type-II phototrophic Chloroflexi are highly abundant and diverse in 60-72ºC hot springs (8,12).…”
Section: Overview Of Site Geochemistry and Metagenome Assembliessupporting
confidence: 93%
See 4 more Smart Citations
“…Similar to psb genes, we recovered more copies of both psc and puf genes in sites < 63ºC, suggesting diversity (or taxa) abundance increases with decreasing temperature. These results are consistent with our previous work that suggest phototrophs with type-I RCs are less abundant at high temperatures, while the type-II phototrophic Chloroflexi are highly abundant and diverse in 60-72ºC hot springs (8,12).…”
Section: Overview Of Site Geochemistry and Metagenome Assembliessupporting
confidence: 93%
“…However, in sites < 63ºC, we recovered more copies of psb genes, suggesting higher alpha diversity within the cyanobacteria population or that single species harbor multiple copies of the psb genes. Previous work has shown that cyanobacterial diversity in alkaline hot springs decreases with increasing temperature and that Leptococcus species, which contain up to three copies of psbA (4) are most abundant in these conditions (8,9,12 Leptococcus A and B 'ecotypes, which respectively occupy temperature ranges of ~55-68ºC and ~50-62ºC, as either A-type or B'-type. Each of the YNP Leptococcus genomes contain two to three variants of the psbA gene, but the environmental conditions that select for strains that harbor multiple copies is unknown.…”
Section: Overview Of Site Geochemistry and Metagenome Assembliesmentioning
confidence: 99%
See 3 more Smart Citations